ANALISIS DIMENSI KUALITAS PELAYANAN PEDAGANG KAKILIMA DAN STARTEGI MENINGKATKAN KEPUASAN WISATAWAN DI MALIOBORO YOGYAKARTA - Ani Wijayanti - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2010)
This research was done to analyze effects of dimension level or variables of service level of retailer dealer toward tourist satisfaction in Malioboro, beside also to analyze variable which have high importance and performance for tourist in Malioboro. This research have hypothesis that said: (1) service level variable that placed at second quadrant is responsiveness, which have high importance and performance. (2) There are positive significant effects between service level variables (reliability, responsiveness, emphaty, assurance dan tangible variables) toward tourist satisfaction. This research used teknik purposive random sampling for sampling method by got any responden between 20-60 years old who had ever visited malioboro. The measuring scale that used are Likert scale by using tourist satisfaction scale and service level scale there are reliability, responsiveness, emphaty, assurance dan tangible variables. To find out more descriptive result of research was used Importance and Performance matrix Analyze, so ascertainabled level of importance every tourist service level variable.This result was used for interested parties references in establish foreigh steps that had taken to increase retailer dealer performance in Malioboro as specifically and retailer dealer in other places for generally. The result of research showed all service level variables (reliability, responsiveness, emphaty, assurance dan tangible variables) have positive effects towards tourist satisfaction by level of significant (α : 5%). The statement answered hypothesis 2 and able to be accepted.Whereas from Importance and Performance Matrix can be shown that responsiveness placed at second quadran it’s meant have high Importance and Performance and hypothesis 1 also be accepted. Keywords :importance, performance, reliability, responsiveness, emphaty, assurance, tangible